2018
DOI: 10.4103/jispcd.jispcd_42_18
|View full text |Cite
|
Sign up to set email alerts
|

Employing dimensional disparity of teeth to establish the gender in Odisha population: A dimorphic study

Abstract: Aims and Objectives:Determination of sex is one of the most important and crucial steps in forensic science. Sexual dimorphism using odontometric analysis is found to vary in different populations making it necessary to attain values of a specific population which helps the identification possible. This present study attempts to establish sexual dimorphism using odontometric analysis in Odisha population.Materials and Methods:A total of 200 subjects (100 male and 100 female) between ages 18 and 25 years were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
1
10
0
2
Order By: Relevance
“…Very few studies were conducted for MD dimension for lateral incisor for sex determination. In the study of Dash KC [ 17 ] right and left maxillary lateral incisor the result were statistically significant with the p value 0.0108 and 0.0009 respectively but for the right and left mandibular lateral incisor result were no significant with the p value 0.2400 and 0.2478. But in our study observation obtained for the maxillary right and left lateral incisor were statistically not significant but for mandibular right and left lateral incisor result statistically significant.…”
Section: Discussionmentioning
confidence: 93%
“…Very few studies were conducted for MD dimension for lateral incisor for sex determination. In the study of Dash KC [ 17 ] right and left maxillary lateral incisor the result were statistically significant with the p value 0.0108 and 0.0009 respectively but for the right and left mandibular lateral incisor result were no significant with the p value 0.2400 and 0.2478. But in our study observation obtained for the maxillary right and left lateral incisor were statistically not significant but for mandibular right and left lateral incisor result statistically significant.…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, symmetrical sexual dimorphism both on the Rt and Lt upper and lower first molars were confirmed . (4,5,6,22) Gender determination of juvenile bony remains is a problem that face forensic experts. Investigating sexual dimorphism of crown traits of the deciduous dentition may help to solve this issue (23) .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the fact that most teeth complete development before skeletal maturation makes them a valuable sex indicator particularly in young individuals . (3) Many studies from various countries and diverse populations have revealed sexual dimorphism of permanent teeth measurements- (4)(5)(6)(7)(8) . Alternatively, few studies involved deciduous dentition in pediatric groups of Spanish, European, south Indian, and Portuguese populations, with inconsistent accuracy (9)(10)(11)(12) .…”
Section: Introductionmentioning
confidence: 99%
“…Measurements are at the core of numerous odontological studies in many disciplines. Traditionally carried out by calipers [10], they increasingly tend to methods, based on 3D imaging, image processing and surface analysis, which is evaluated positively in comparative studies [11]. At a minimum it is possible to use general advantages of digital methods by application of traditional techniques to 3D reconstructions of tooth surfaces [12].…”
Section: Related Workmentioning
confidence: 99%